Plum Island Coffee Roasters: a perfect blend of coffee, business and community. Issue 2 (5th May 2016) - Foudray, Gregory C.
Abstract : Synopsis: The owner of an independent coffee shop is looking for methods to improve the sales performance of his business. He has strong customer sales and service skills but limited formal business education. He believes his sales are growing but seasonal volatility in sales is affecting his profitability. The manager of the coffee shop is a college student and is attempting to use methods from her business courses to analyze the impact of Facebook Advertising on the sales of the coffee shop. On a busy Friday in May, they are meeting to make key marketing decisions. Research methodology: This case is a field researched case. The author had full access to the owner of the business, meeting with him frequently over a two-year period. The business owner has reviewed the case to verify its accuracy. Relevant courses and levels: This case is intended for use in undergraduate business courses in the subject areas of Business, Marketing and Social/Digital Media Marketing.